POSITIVE PREDICTIVE VALUE OF RADIOLOGICAL KNEE EFFUSION SIZE IN TRAUMATIC KNEE INJURY IN PREDICTING INTERNAL DERANGEMENT TAKING MAGNETIC RESONANCE IMAGING AS GOLD STANDARD". - Dr. Ayesha Khalid; Dr. Faiza Farooq; Dr. Khadija Ashraf; Dr. Hamna Ashraf; Lala Rukh; Amara Arshad (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Objective: This study sought to investigate whether the size of knee effusion visible on X-rays can effectively predict internal knee injuries in children with trauma, using MRI as the reference standard for diagnosis. Methods: A cross-sectional study was performed at the Department of Diagnostic Radiology in Children’s Hospital Lahore from October 29, 2019, to April 28, 2020. The sample included 101 children, aged 4 to 12 years, of both genders, who presented after knee trauma with suspected internal knee injuries indicated by knee effusion (≥1 cm in anteroposterior diameter on lateral X-ray). The diagnosis was confirmed through MRI, which served as the gold standard. Each X-ray was evaluated for knee effusion, categorizing the findings as true positive or false positive. Informed consent was obtained from the parents of all participating children. Results: The average age of the participants was 8.6 years, with a standard deviation of 2.4 years. Among the participants, 73 (72.3%) were boys and 28 (27.7%) were girls, resulting in a male-to-female ratio of 2.6:1. Internal knee injuries were confirmed in 93 children (92.1%) via MRI. The study revealed a positive predictive value of 92.1% for knee effusion detected on X-rays in predicting internal knee injuries, a value that was consistent across various subgroups based on age, gender, and weight. Conclusion: The findings indicate that knee effusion size on X-rays holds a high positive predictive value (92.1%) for identifying internal knee injuries in pediatric trauma cases, as confirmed by MRI. The advantages of X-rays—being quick, non-invasive, cost-effective, and widely available—support their use in assessing children with knee injuries in clinical practice.